Cell migration and the ganglioside composition of the cell lines derived from Reuber hepatoma - Dudková, Lenka; Muchová, Lucie; Brožová, Eva; Šmíd, František (Journal of Applied Biomedicine, 2007)
The migration potency of differentiated (H-4-II-E, H-4-II-E-C3) and dedifferentiated (H-5) cell lines originated from Reuber hepatoma H 35, and their connection to the morphology and expression of gangliosides were examined. The migration capacity tested by a Transwell assay was fifteen times higher in H-5 cells compared to H-4-II-E cells. The ganglioside pattern was assessed by thin-layer chromatography (TLC). H-4-II-E and H-4-II-E-C3 cell lines expressed Fuc-GM1, which was not found in H-5 cells, whereas H-5 expressed GM3, which was absent in differentiated cell lines. GM3 ganglioside is thought to be one of the key molecules involved in signal transduction of mammalian cells. We conclude that changes in the migration capacity of various hepatoma cell lines might relate to their ganglioside spectra.
Keywords: G(M3) gangliosid; krysa rodu Rattus; Animals; G(M3) Ganglioside; pohyb buněk; chromatografie na tenké vrstvě; gangliosidy; zvířata; Cell Movement; Gangliosides; Chromatography, Thin Layer; Cell Line, Tumor; experimentální nádory jater; Liver Neoplasms, Experimental; Rats; nádorové buněčné linie